2011
DOI: 10.1007/s10384-011-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculotomy combined with phacoemulsification, intraocular lens implantation and sinusotomy for exfoliation glaucoma

Abstract: PTOS can be recommended as an initial glaucoma surgery for XFG eyes with coexisting cataracts, because PTOS is not a filtering surgery, but can obtain similar IOP effects as PTE for XFG eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Previous studies reported that ab externo TLO achieved mean postoperative IOPs ranging from 12.3 to 18.4 mm Hg,3–5 while Tanito et al showed that ab interno TLO had a mean postoperative IOP of 11.8±4.5 mm Hg at 9.5 months postoperatively 14. Compared with these reports, our present postoperative IOP at 1 year was higher in both procedures ( ab externo TLO: 18.3±7.4 mm Hg, ab interno TLO: 17.8±6.3 mm Hg).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Previous studies reported that ab externo TLO achieved mean postoperative IOPs ranging from 12.3 to 18.4 mm Hg,3–5 while Tanito et al showed that ab interno TLO had a mean postoperative IOP of 11.8±4.5 mm Hg at 9.5 months postoperatively 14. Compared with these reports, our present postoperative IOP at 1 year was higher in both procedures ( ab externo TLO: 18.3±7.4 mm Hg, ab interno TLO: 17.8±6.3 mm Hg).…”
Section: Discussioncontrasting
confidence: 53%
“…In ab externo TLO, the Schlemm’s canal is identified either by peeling off a scleral flap or by making an incision in the scleral wall over the Schlemm’s canal before a metal probe is inserted into the canal and rotated into the anterior chamber to perforate the inner wall of the canal. The ab externo TLO procedure has been shown to reduce intraocular pressure (IOP) not only in patients with childhood glaucoma1 2 but also in adult patients with primary open angle glaucoma (POAG), steroid glaucoma and exfoliation glaucoma, at early stages 3–5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trabeculotomy (LOT) is a type of nonpenetrating surgery that involves opening Schlemm’s canal over 120°. It is effective not only for exfoliation glaucoma and congenital glaucoma,4,13 but also for primary open angle glaucoma (POAG) 5,6,10,13. In addition, it has been found to further reduce the IOP when performed in combination with cataract surgery 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…It is effective not only for exfoliation glaucoma and congenital glaucoma,4,13 but also for primary open angle glaucoma (POAG) 5,6,10,13. In addition, it has been found to further reduce the IOP when performed in combination with cataract surgery 4,5. Moreover, LOT combined with cataract surgery and deep sclerectomy (DS) has been found to achieve the same surgical outcomes as trabeculectomy with cataract surgery 6…”
Section: Introductionmentioning
confidence: 99%